Historic urban landscape. Methodological suggestions for the management plan of the historic district of Buenos Aires - González Biffis, Alejandra (2022)
The most recent approaches to historic centers propose the need to understand these sectors by incorporating the concept of historic urban landscapes. This term proposes an integral perception of the city and its surroundings, its historical physical-environmental, sociocultural and economic processes; in addition, it encourages the incorporation of contemporary architecture, respecting the inherited urban landscape, its landscape environment and sustainable urban development. In this context, the present study confronts the Management Plan for the Historic District of Buenos Aires (2015) -as a planning instrument- with the Methodology for the valuation, intervention and management of historic urban landscapes -as an academic instrument-. The objective is to put forward suggestions that can be applied to the Management Plan, and thus have a normative instrument that incorporates the notion of historic urban landscapes.